Engaging and partnering with Aboriginal and Torres Strait Islander parents and caregivers : final report. - White, Simone; Anderson, Peter; Gower, Graeme; Byrne, Matt; Bennet, Maria; Quin, Alison; Darling, Anna (Australia. Dept of Education and Training (DET), 2019)
The Engaging and partnering with Aboriginal and Torres Strait Islander parents and caregivers two-year project has culminated in a unique interactive website that houses a number of learning and teaching tools, strategies and resources designed to support all those working to improve the educational success of Aboriginal and Torres Strait Islander students in schools, Australia's First Nations peoples. It is intended to be used in teacher education programs (pre-service and in-service), by teachers and school leaders, and by Aboriginal and Torres Strait Islander communities. The resource has been created to help all educators form relationships and partnerships with local communities, parents and caregivers to achieve better educational outcomes for all Aboriginal and Torres Strait Islander students. The resource positions educators as powerful agents of change. The project began from the premise that school education has traditionally involved ways of thinking and learning imposed on Aboriginal and Torres Strait Islander people, more often than not with little to no opportunity for input or collaboration. The project has built on the momentum for reconciliation and change, drawing from institutional recommendations in the Australian Government's Review of Higher Education Access and Outcomes for Aboriginal and Torres Strait Islander People, Final Report (2012). Professional development in regards to addressing these standards is acknowledged as vitally important and funding to date has supported a number of 'partnership' resources that have already been created and developed to educate teachers about Aboriginal and Torres Strait Islander peoples and culture. Up to this point, however, these resources appear to be underutilised, with many teachers, teacher educators, leaders and pre-service teachers still either unaware of or ill-equipped for the best ways to ensure better outcomes for all Aboriginal and Torres Strait Islander students. As a consequence, partnerships between schools, teacher education providers and communities continue to suffer and can appear fragile and difficult to develop. The challenge for this project, therefore, has been to develop a fresh approach to professional development and reconciliation and, ultimately, to produce a 'go to' resource for all teacher education providers, schools and communities, tailored to diverse individual learning needs. Rather than (re)produce another partnership resource as a product, an iterative, inquiry learning approach has been adopted, culminating in an interactive website resource that powerfully connects the learner to resources for their context. [Executive summary, ed]